Curriculum development system : a handbook for school practitioners in basic education - Palma, Jesus C. (Mandaluyong City : National Book Store, 1992)
This handbook evolved from the random notes compiled and collated by the writer for the numerous seminar-work shops on curriculum and instruction he has conducted in various elementary and secondary school settings in different parts of the country for almost a decade. What started as a professional outreach activity in commemoration of the quadricentennial of the coming of the Jesuits to the Philippines in 1980, became an on-going, long-playing series brought about. by the enthusiastic response of many schools and professional organizations. After a while, the writer finally acceded to the recurring suggestion of many well-meaning beneficiaries of the program to put the notes in print form "for posterity" and to reach a wider audience. Hence, this opus.
Chapter One. CDS conceptual framework -- Chapter Two. School purpose -- Chapter Three. Curriculum content -- Chapter Four. Learning experiences and resources -- Chapter Five. Evaluation of learning.
Includes bibliographical references and index.
Keywords: CURRICULUM CHANGE